The development of baking technology for bulk materials based on the use of alternative electric furnace - Nizhegorodov, A.; Gavrilin, A.; Moyzes, B.; Kuvshinov, K. (KSU Publ., 2020)
The article based on the experimental data and it describes the development of a rational design of an oscillatory system for controlled vibrational feeding of bulk materials during their heat treatment in furnaces with a vibratory base plate, which, together with the moving trolley on elastic connections, is the basis to transfer bulk material in the thermal field of an electric heating system with set processing time. To create nonsymmetric oscillations and to obtain unidirectional material motion at the horizontal furnace position, the conical springs are used. They should provide a gently inclined resonant peak, which can significantly reduce the sensitivity of the oscillating system to fluctuations of the natural frequency and excitation frequency, stiffness, friction and other factors under high temperatures and instability of the electrical network. However, the total elastic characteristic of the oscillatory system which is obtained as a result of the experiments consists of conical and cylindrical springs and shows a weakly expressed nonlinearity. Therefore, to achieve a transport effect it will require the installation of the entire furnace unit at an angle to the horizon. According to the available experimental data, a linear model of the oscillatory system was utilized.
Баламалы электрпешті пайдалану негізінде сусымалы материалдарды күйдіру технологиясын əзірлеу
Разработка технологии обжига сыпучих материалов на основе использования альтернативной электропечи
Keywords: an electric furnace for bulk materials burning; vibrating base plate; oscillating system; nonlinear elastic characteristic; amplitude-frequency characteristic; sensitivity of the oscillating system to external factors